Vad händer i fritidshemmet? - Helene Elvstrand; Lina Lago; Magnus Jansson (Educare)
This study examines pupils’ experiences of activities in Swedish school-age educare (SAEC) by exploring the identified tension between mandatory and free activities in relation to participation. In recent years, there has been a shift from a social pedagogical starting point to education and learning in SAEC settings which has implications for the kind of activities that take place. The study contributes to knowledge of pupils’ perspectives on SAEC teaching using qualitative methods, fieldwork and interviews, with pupils in the ages between 7 and 9 at six different SAEC centres. The theoretical framework for the study is childhood sociology. Data has been collected and treated in accordance with a grounded theory approach. The results show that free activities are perceived more positively by the pupils than mandatory activities. However, whether an activity is perceived as meaningful also needs to be linked to other aspects, for example in pupils’ experiences of SAEC activities, the tension between mandatory and free activities intersects with comprehensibility and forms of participation leading to more positive experiences of activities that are framed in a way that is in line with the pupils’ expectations of SAEC activities or activities that enable active participation for the pupils.